Good Teaching Starts Here: Applied Learning at the Graduate Teaching Assistant Institute - Parker, Michele A.; Ashe, Diana; Boersma, Jess; Hicks, Robert; Bennett, Victoria (Canadian Journal of Higher Education, 2015)
Increasingly, graduate teaching assistants serve as the primary instructors in undergraduate courses, yet research has shown that training and development for these teaching assistants is often lacking in programs throughout the United States and Canada. Providing mentoring and skill development opportunities for graduate teaching assistants is vital, as many will become the next generation of faculty. This paper discusses the literature on effective training programs, which underscores the importance of consistent feedback from mentors, intrinsic motivation, and practical applications. Afterwards, we examine an existing training program at the University of North Carolina Wilmington. Specifically, we focus on an institute for teaching assistants that helps graduate students understand applied learning as an effective pedagogical modality and helps them implement applied learning lesson plans tailored to their disciplines. Suggestions for strengthening training programs are discussed.